When unconscious rewards boost cognitive task performance inefficiently: the role of consciousness in integrating value and attainability information - Zedelius, Claire; Veling, Harm; Aarts, Henk (Frontiers in Human Neuroscience, 2012)
Research has shown that high vs. low value rewards improve cognitive task performance independent of whether they are perceived consciously or unconsciously. However, efficient performance in response to high value rewards also depends on whether or not rewards are attainable. This raises the question of whether unconscious reward processing enables people to take into account such attainability information. Building on a theoretical framework according to which conscious reward processing is required to enable higher level cognitive processing, the present research tested the hypothesis that conscious but not unconscious reward processing enables integration of reward value with attainability information. In two behavioral experiments, participants were exposed to masked high and low value coins serving as rewards on a working memory task. The likelihood for conscious processing was manipulated by presenting the coins relatively briefly (17 ms) or long and clearly visible (300 ms). Crucially, rewards were expected to be attainable or unattainable. Requirements to integrate reward value with attainability information varied across experiments. Results showed that when integration of value and attainability was required (Experiment 1), long reward presentation led to efficient performance, i.e., selectively improved performance for high value attainable rewards. In contrast, in the short presentation condition, performance was increased for high value rewards even when these were unattainable. This difference between the effects of long and short presentation time disappeared when integration of value and attainability information was not required (Experiment 2). Together these findings suggest that unconsciously processed reward information is not integrated with attainability expectancies, causing inefficient effort investment. These findings are discussed in terms of a unique role of consciousness in efficient allocation of effort to cognitive control processes.